Comparative morphology of stridulating setae of Theraphosinae (Araneae: Theraphosidae) - Galleti-Lima, Arthur [UNESP]; Guadanucci, José Paulo Leite [UNESP] (Elsevier, 2019)
Theraphosid spiders are repleted with cuticular structures that evolved into distinct morphologies and developed different functions. The stridulatory apparatus present in the subfamily Theraphosinae is composed by a group of setae and opposed organs (ridged surface) that emit sound through friction. Only sixteen genera of Theraphosinae spiders were reported with stridulatory setae: Acanthoscurria, Aguapanela, Brachypelma, Citharacanthus, Cyrtopholis, Grammostola, Hemirrhagus, Lasiodora, Longilyra, Nhandu, Theraphosa, Pamphobeteus, Phormictopus, Proshapalopus, Pterinopelma and Vitalius. Besides these stridulating setae, other cuticular structures have been traditionally used in Theraphosinae taxonomy: the plumose scopula on the lateral faces of femora I and IV. However, the ultrastructure of these setae and scopulae was never studied in detail. Here, we analyzed the diversity of cuticular structures on coxae, trochanters and femora of Theraphosinae spiders using SEM. Beside the description of plumose and claviform stridulating setae on femora, we established five distinct variations of stridulatory setae found on coxae and trochanters and report their presence for the genus Megaphobema, Crassicrus and Cotztetlana for the first time.
Keywords: SEM; Stridulation; Tarantula; Ultrastructure